BBC News Yoruba and digital public sphere: promoting Yoruba cultural traditions among youths of South-West Nigeria - Bakenne, Nureni Aremu; Salawu, Abiodun (Penerbit Universiti Kebangsaan Malaysia, 2025)
This paper examines the impact of the BBC News Yorùbá on the promotion of Yorùbá cultural traditions among youths of the South-West Nigeria. Research has established that youths of today are, perhaps, the most significant users of social media and they have the liberty and ability to make their own choices through the platform. Thus, this study poses the question of how much the media influences their choices. The study aims to investigate the relationship between BBC News Yorùbá and the promotion of Yorùbá language among the youths, particularly those of the South-West Nigeria and how the medium is used for the rejuvenation of Yorùbá language among them. It was revealed that indigenous languages play a significant role in the revitalisation of mother tongue, with respondents agreeing that the BBC News Yorùbá has reawakened their consciousness towards the cultural capital of their language. Employing cultural effects theory, the study utilised survey research design, while purposive sampling was also used to elicit data from the youth population in Lagos, Oyo and Ondo States through the distribution of 1,200 questionnaire copies Findings show that the establishment of the BBC News Yorùbá is a timely intervention in the drive towards the revitalisation of Yorùbá language. It is thus recommended that concerned stakeholders should make concerted efforts towards the development and standadardisation of Nigerian indigenous languages.